Mega-sporting events as experience goods - Malte Heyne; Wolfgang Maennig; Bernd Süssmuth (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2007)
This paper tests the hypothesis that a nation's hosting of a mega-sporting event is an experience good for its residents. Applying data from an ex-ante and ex-post query based on contingent valuation methods, we use the Soccer World Cup 2006 as a natural experiment. The significant ex-post increase in valuation is shown to be due to adventitious citizens requiring an involving experience, rather than to an updating of aprior assessment.
Keywords: L83; Q26; H49; 330; Experience goods; contingent valuation method; World Cup